Practical Design of Flow Meter for Mechanical Ventilation Equipment - Dugarte, Nelson (2021)
This paper introduces a practical technique for the design of an instrument used in air flow measurement or flowmeter. This instrument is an essential component in the hospital medical ventilation equipment functioning, therefore, the parameters design presented in this article focus on this purpose. However, this instrument can be employed to any measurement scale. The technique is based on indirect flow measurement, using a sensor that converts the flow parameter into a differential pressure measurement. An electronic transducer allows the differential pressure values to be obtained as an electrical signal, which is then digitized and analyzed to obtain the original parameter. The experimental procedure presented in this paper utilizes a computational algorithm to perform the signal analysis; however, given the simplicity of the procedure, this could be adapted to any digital processing card or platform, to show the measurement obtained immediately. Preliminary analyses demonstrated instrument efficiency with sensitivity of 0.0681 liters per second (L/s). Accuracy evaluation showed an average measurement error lesser than 1.4%, with a standard deviation of 0.0612 and normal distribution over the set of test measurements.